SINERGITAS KINERJA GURU PAI DAN PENGAWAS DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMP PROVINSI SULAWESI BARAT - wardiah hamid (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This reseach aims to explore and uncover synergy with the supervisory teacher performance in relation to improving the quality of learning in Junior High School in West Sulawesi. This reseach will be approached using a quantitative method with survey approach. This reseach used a questionnaire to collect data relating to the performance of supervisors and teachers of PAI to synchronise for find synergy with the performance of both.Synergy of The data obtained will be used to describe the characteristics of the synergy between populations (Teachers of PAI and Supervisors). The Research shows that the proportion of the balance of the teachers and superintendents in Polman and Majene uneven where supervisors amounted to only 5 people while teachers of PAI 121 people. Synergy of PAI’s teachers performance and superintendents in Polewali Mandar and Majene on profetional aspect, pedagogic aspects, aspects of leadership suprervisi academic supervisor, supervisor evaluation aspects in general are at the level of medium quality, except for aspects of research and the level of development are very low quality. Some supporting factors and obstacles in the implementation of the basic tasks and functions of teachers and supervisors motivating factors, among others, the school environment that supports learning of PAI implemented in containers MGM communications that facilitate synergy between teachers and supervisors. Factor inhibitors time of teaching The Islamic studies are in the limit, vast distances and remote result watchdog could not reach the schools.